The importance of emotional intelligence in the management of stress at work - Hamulić Ramiza; Bajrić Amela; Sivić Mujo; Bajrić Ajla (Scripta Medica)
Emotional intelligence is the ability to recognise one's own and other people's emotions and adjust one's behaviour in accordance with them. Numerous studies have shown that emotional intelligence has a positive effect on job satisfaction, employee performance, interpersonal relationships, business communication and productivity. In today's fast-paced and competitive business world, the ability to understand and manage one's own emotions, as well as the emotions of others, becomes crucial for building professional relationships. Emotionally intelligent people cope more easily with acute and chronic stress, which directly affects mental health and work performance. Using emotional intelligence as a tool to reduce stress in the workplace, as well as to resolve conflicts that have cause-and-effect relationships, allows for a better understanding of the needs and feelings of employees. The ability to effectively manage emotions and stressful situations can significantly contribute to employee satisfaction and loyalty, that is crucial to long-term business success.